Isolation and partial characterization of a chloride channel gene which is expressed in kidney and is a candidate for Dent's disease (an X-linked hereditary nephrolithiasis). - Fisher, S; Black, G; Lloyd, SE; Hatchwell, E; Wrong, O; Thakker, R; Craig, I (1994)
Dent's disease, an X-linked renal tubular disorder, is a form of Fanconi syndrome which is characterized by proteinuria, hypercalciuria, nephrocalcinosis, kidney stones and renal failure. Previous studies localised the gene responsible to Xp11.22, within a microdeletion involving the hypervariable locus DXS255. Further analysis using new probes which flank this locus indicate that the deletion is less than 515 kb. A 185 kb YAC containing DXS255 was used to screen a cDNA library from adult kidney in order to isolate coding sequences falling within the deleted region which may be implicated in the disease aetiology. We identified two clones which are evolutionarily conserved, and detect a 9.5 kb transcript which is expressed predominantly in the kidney. Sequence analysis of 780 bp of ORF from the clones suggests that the identified gene, termed hCIC-K2, encodes a new member of the CIC family of voltage-gated chloride channels. Genomic fragments detected by the cDNA clones are completely absent in patients who have an associated microdeletion. On the basis of the expression pattern, proposed function and deletion mapping, hCIC-K2 is a strong candidate for Dent's disease.